PENGELOLAAN DANA DESA DALAM UPAYA MEMINIMALISIR KEMISKINAN DI DESA JANJI KECAMATAN BILAH BARAT KABUPATEN LABUHANBATU - Kartadinata, Rizkika; Windawati Pinem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the management of village funds in an effort to minimize poverty in Janji Village, West Bilah District, Labuhanbatu Regency. The problem in this study is the unstable decline in the poverty rate. Poverty rate data in Janji Village, West Bilah District, Labuhanbatu Regency has increased over the past 3 years, namely in 2021 there was a poverty rate of 431 people, in 2022 the poverty rate was 720 people and in 2023 the poverty rate was 1000 people and a decrease in poverty in 2024 was recorded at 880 people. The issue of poverty in Janji villages is not only seen in economic terms, but also as a multidimensional problem involving cultural, pedagogical and social aspects. The research used qualitative research, descriptive methods, data obtained through in-depth interviews, observation and documentation on the population and research samples, namely the village government and the community receiving social assistance. The results showed that the management of village funds in an effort to minimize poverty in Janji Village, West Bilah District, Labuhanbatu Regency was “Quite Optimal” because village funds contributed positively to the sustainability of community empowerment programs in agriculture and animal husbandry. The impact on the poverty rate in Janji Village has decreased by 120 people in the 2023-2024 period as a result of the implementation of empowerment programs in the agricultural and livestock sectors that are carried out periodically. The program has been implemented since the beginning of 2023. In the previous period, 2022-2023, the poverty rate in the village actually increased by 280 people, despite being led by the same village head. However, at that time there was no structured and sustainable empowerment program. The success in reducing poverty in 2023-2024 confirms that empowerment programs, such as agriculture and animal husbandry, play a significant role in improving the welfare of residents, but there are still some obstacles to the equity (inclusiveness) of community empowerment programs that need to be improved to achieve full optimality. This research recommends increasing the participation of all levels of society and developing more inclusive programs to achieve full optimality in minimizing poverty in Janji Village.